A systematic literature review of Islamic inheritance in Malaysia - Norhazlina Ibrahim; Khairatun Hisan Idris Shazali; Rusgianto, Sulistya (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study aims to expand the existing body of knowledge by highlighting and summarising current studies on Islamic inheritance. Thus, this study presented a map of the research interest and determined primary issues to demonstrate current trends, future research directions, and theory development. A systematic literature review (SLR) approach was employed using the four-step reporting standard for the Systematic Evidence Syntheses (ROSES) review: research question formulation, systematic searching, quality assessment, and data extraction. A total of 33 screened articles between 2008 and 2022 were retrieved from two primary databases (Scopus and Emerald and one supporting database, Google Scholar). The factors were categorised into three primary themes: general, motives and preference studies, and determinant analysis. The themes were subsequently divided into seven sub-themes. Notably, most studies examined unclaimed asset issues based on the determinant analysis. This study offered useful insights into the current research interest regarding the subject. The issues and domains in the current study contribute new knowledge and theory development for future directions in the field. This study addressed empirical gaps and presents an excellent reference relevant for regulators, policymakers, and researchers in comprehending the issues and existing solutions in Islamic inheritance.